2015
DOI: 10.1021/acsmacrolett.5b00102
|View full text |Cite
|
Sign up to set email alerts
|

Nonhemolytic and Antibacterial Acrylic Copolymers with Hexamethyleneamine and Poly(ethylene glycol) Side Chains

Abstract: Amphiphilic acrylic copolymers with hexamethyleneamine and poly­(ethylene glycol) side chains can show >100-fold selectivity toward Escherichia coli over red blood cells. Homopolymer with cationic pendant amine groups is highly hemolytic and antibacterial. Incorporation of approximately 33 mol % of poly­(ethylene glycol) methyl ether methacrylate (PEGMA) led to 1300 times reduction in hemolytic activity, while maintaining high levels of antibacterial activity. The hemolytic activity of these PEGylated copolyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
56
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(61 citation statements)
references
References 30 publications
4
56
1
Order By: Relevance
“…43 Punia et al have also reported that when increasing the cationic and hydrophobic components of an antibacterial copolymer there was a concomitant increase in haemolysis. 44 These results demonstrate that it is critically important for the proportion of cationic and hydrophobic residues in cationic antibacterial polymers to be optimised to allow selective killing of bacteria with minimal effect on mammalian cells. 45 …”
Section: Resultsmentioning
confidence: 87%
“…43 Punia et al have also reported that when increasing the cationic and hydrophobic components of an antibacterial copolymer there was a concomitant increase in haemolysis. 44 These results demonstrate that it is critically important for the proportion of cationic and hydrophobic residues in cationic antibacterial polymers to be optimised to allow selective killing of bacteria with minimal effect on mammalian cells. 45 …”
Section: Resultsmentioning
confidence: 87%
“…The results suggest that these copolymers are bacteriostatic (or growth inhibiting) against both E. coli and S. aureus, and the MIC values of these copolymers against E. coli and S. aureus seem to approach a comparable level with other quaternized PDMAEMA copolymers. 40 This phenomenon presumably is due to the fact that S. aureus has a very thick (20-80 nm) and highly crosslinked peptidoglycan layer (polysaccharide with amino acid side chains) in the outer cell wall, 41 which may interact with Agr polysaccharide via hydrogen bonding to retard the permeation of the Agr-based copolymers as well as the disruption of cellular membrane. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…33,38 To further ascertain the bactericidal activities of these copolymers, their timedependent killing efficiencies were assayed by co-culturing them at 1 Â MIC and 2 Â MIC concentrations with E. coli and S. aureus. The peptidoglycan layer between the outer and inner membrane of E. coli has a thickness of 6-8 nm, 40 and may not be sufficient to hinder the polymer permeation. 3a and b, signicant loss of viable E. coli and S. aureus are observed.…”
Section: Resultsmentioning
confidence: 99%
“…Protonated primary amines and protonated tertiary amines of polyacrylates were more antimicrobial and less hemolytic than quaternary amines, and similar results were observed for poly(methacrylamide) . Protonated primary amines in aminohexyl polyacrylate showed strong antimicrobial activity with MIC of 6.5 µg/mL for Gram‐negative E. coli and 16 µg/mL for Gram‐positive S. aureus . Furthermore it was observed that primary amines of low molecular weight polyacrylate showed antimicrobial activity but the corresponding quaternary amines lost the activity probably due to loss of hydrophobicity needed to disrupt the cell membranes of pathogens .…”
Section: Introductionmentioning
confidence: 55%
“…However, hydrophilic units were also introduced. Copolymerization of PEG acrylate with aminohexyl acrylate could reduce the hemolytic activity significantly but showed less effect on antimicrobial activity, for example, about 33 mol % of PEG methacrylate led to 1300 times reduction in hemolytic activity, while maintaining high levels of antibacterial activity . Also incorporation of certain amount of glycol‐units into quaternary ammonium containing polyacrylate reduced cytotoxicity without significant effects on antimicrobial activity …”
Section: Introductionmentioning
confidence: 99%